Changes in magnetic order through two consecutive dehydration steps of metal-phosphonate diamond chains. Issue 55 (7th October 2019) - Su, Yan-Hui; Jia, Jia-Ge; Huang, Xin-Da; Feng, Jian-Shen; Bao, Song-Song; Ren, Min; Kurmoo, Mohamedally; Zheng, Li-Min
Abstract : M3 II (hpdpH)2 (H2 O)6 ·4H2 O (M = Co, Ni) experience identical two-step dehydration processes associated with drastic magnetic changes from paramagnet to antiferromagnet/metamagnetic to ferrimagnet for M = Co, and from antiferromagnet to antiferromagnet to ferrimagnet for M = Ni. Abstract : Hydrothermal reactions of the multitopic ligand 1-hydroxy-1-(piperidin-4-yl)methylidenebisphosphonic acid (hpdpH4 ) with cobalt or nickel sulfates afforded two new isostructural metal phosphonates, M3 II (hpdpH)2 (H2 O)6 ·4H2 O [M = Co (Co-10H2 O ), Ni (Ni-10H2 O )]. Their structures consist of parallel diamond chains of three MO6 octahedra bridged by the PO3 C tetrahedra. Six of the seven oxygen atoms of the ligand are involved in coordination; for two ligands that amounts to 12 bonds for 3 MO6 and the remaining six are occupied by terminal water molecules. In addition, four water molecules sit in between the chains providing H-bonds to the formation of a 3D-net. Thermal analyses show identical two-step dehydration processes involving first the departure of six water molecules followed by the remaining four. A detailed study of the ac- and dc-magnetization as a function of temperature, field and frequency reveals associated drastic changes. The virgin form Co-10H2 O is a paramagnet while its partial dehydrated form Co-4H2 O is an antiferromagnet displaying canting below T N = 4.7 K and the fully dehydrated form Co is a ferrimagnet ( T C = 12 K). Ni-10H2 O and Ni-4H2 O exhibit long-range ordered antiferromagnetism ( T N = 2.7 and 4.0 K, respectively) and also become ferrimagnets ( T C = 9.4 K) when fully dehydrated to Ni . The dehydrated samples can be fully rehydrated with the complete recovery of both the structures and magnetic properties.